Effective And Safe Use Of Cephalosporins In The Treatment Of Urinary Tract Infection - Khakberdiyeva Gulzhakhon Erkinovna; Kasimova Shakhlo Shavkatovna; Shirina Abrarovna Abdurazakova (Zien Journals, 2024)
The high prevalence of urinary tract infections (UTIs) determines their high significance, not only medical, but also social. Every year, UTIs are the cause of outpatient visits and emergencyя medical care from the hospital[й [1]. Recently, it has been found that причиной UTI is caused уропатогенныеby uropathogenic E. Colistrains. ТакжеAn increase in the frequency of infections caused by gram-negative microorganisms was also noted, and therefore a further search for new drugs among cephalosporin antibiotics was aimed дляat creating drugs with increased activityagainst these microorganisms. New cephalosporin antibiotics are needed because of the huge increase in the number of drug-resistant bacteria
Keywords: antibacterial prevention; antibacterial drugs; urological operations